Regulatory intervention to ensure an efficient medium-term planning in electricity markets - Rodilla Rodríguez, Pablo; Baillo Moreno, Alvaro; Batlle López, Carlos; Cerisola Lopez De Haro, Santiago (My University, 2016)
In the context of the security of electricity generation supply problem, the electric power system firmness has been defined as the ability of already installed facilities to supply electricity efficiently in the medium term. In other words, the firmness represents the ability of the system to supply electricity efficiently within a time term in which the system cannot count on new investments to solve the security of supply problem, e.g. one or two years. This ability depends to a large extent on how generators carry out their medium-term resource planning (implying among others fuel provision, water reservoir management or maintenance scheduling). In this paper, on the basis of a stylized mathematical model developed specifically for this purpose, we contribute from the regulator’s point of view to the theoretical analysis and discussion of the firmness dimension in a market environment. We focus on how generators’ risk aversion coupled with generators' inability to efficiently hedge long-term positions (due to market incompleteness) may lead the system towards an inefficient (from the social perspective) outcome. In this context, we evaluate whether some kind of regulator’s intervention could be recommended in order to lead the market towards a more efficient/adequate solution. This intervention, as already implemented in certain electric power systems, could (and in some power markets does) take the form of administratively setting minimum hydro reservoir levels or compulsory long-term contracting.

In the context of the security of electricity generation supply problem, the electric power system firmness has been defined as the ability of already installed facilities to supply electricity efficiently in the medium term. In other words, the firmness represents the ability of the system to supply electricity efficiently within a time term in which the system cannot count on new investments to solve the security of supply problem, e.g. one or two years. This ability depends to a large extent on how generators carry out their medium-term resource planning (implying among others fuel provision, water reservoir management or maintenance scheduling). In this paper, on the basis of a stylized mathematical model developed specifically for this purpose, we contribute from the regulator’s point of view to the theoretical analysis and discussion of the firmness dimension in a market environment. We focus on how generators’ risk aversion coupled with generators' inability to efficiently hedge long-term positions (due to market incompleteness) may lead the system towards an inefficient (from the social perspective) outcome. In this context, we evaluate whether some kind of regulator’s intervention could be recommended in order to lead the market towards a more efficient/adequate solution. This intervention, as already implemented in certain electric power systems, could (and in some power markets does) take the form of administratively setting minimum hydro reservoir levels or compulsory long-term contracting.